Bribery in subsidized credit markets: evidence from Bangladesh. Issue 1 (8th April 2014) - Dechenaux, Emmanuel; Lowen, Aaron; Samuel, Andrew
Abstract : Purpose: – The aim of this paper is to study the role of bribery in subsidized credit markets in developing countries. First, the authors use the data to test whether more productive borrowers will pay larger or smaller bribes since the theoretical literature offers conflicting findings regarding the relationship between the size of the bribe and the productivity of borrowers. Second, the authors test whether being eligible to borrow from a microfinance institution affects the frequency or the magnitude of the bribe paid when borrowing from a (non-microfinance) subsidized bank. Design/methodology/approach: – The empirical analysis is based on existing theoretical models of bribery. The data set uses publicly available survey data from the Bangladesh Institute for Development Studies. The primary linear model is estimated using OLS. Because left-censoring affects the data, the authors also estimate a Tobit model. Finally, to correct for potential selection bias, the authors also estimate a Heckman selection model. Findings: – The authors find that more productive borrowers pay lower bribes than less productive borrowers and that being MFI-eligible affects the frequency of bribery, but not the magnitude of the bribe. Originality/value: – To the authors' knowledge, the paper is the first empirical study of bribery in subsidized credit markets.